Du Pont System: Comparative Study Of Financial Performance PT. Indosat Tbk and PT. XL Axiata Tbk - M. Boy Singgih Gitayuda; Arie Setyo Dwi Purnomo (Trunojoyo University of Madura, 2020)
The level of competition of telecommunications companies is getting tougher. Net income is one reference to measure the company's financial condition through the company's financial performance. This research will compare the two companies so that it can be known which company performance is better in that year and what influences it. The research method used is a quantitative method with a descriptive approach. This study uses secondary data types obtained from the Indonesia Stock Exchange. Researchers used the DuPont System analysis technique in conducting data analysis. Return on Investment (ROI) in the 2017 and 2019 period PT Indosat Tbk experienced a decline in ROI compared to 2017, this indicates that the level of net income obtained by the company owner for the capital invested in the company decreased. Return on Equity (ROE) in the 2017 and 2019 periods of PT XL Axiata Tbk has increased from 1.69 to 3.7, this indicates that the management of PT XL Axiata is able to provide better gains for shareholders.